Hasil belajar mahasiswa calon guru biologi pada praktikum sistematika invertebrata selama masa pembelajaran tatap muka terbatas 2021/2022 - Hastin Puspitasari; Putri Agustina (Bio-Pedagogi : Jurnal Pembelajaran Biologi, 2023)
ENThis study aims to determine the learning outcomes of prospective biology teacher candidates for the biology education study program at the a University in Surakarta during the limited PTM period T.A 2021/2022. This type of research is ex post facto research. The subjects of this study were 145 students who took the Invertebrate Systematics practicum course. The data of this study were obtained from the documentation of student learning outcomes and then analyzed by descriptive analysis. The results showed that the learning outcomes of Invertebrate Systematics practicum students during the limited PTM period T.A 2021/2022 of the three components were generally in the medium category. The posttest results obtained an average of 69.6, the response test with an average of 63.2 and the average final practicum score was 75.6. This shows that student learning outcomes during the limited PTM period are quite good. IDPenelitian ini bertujuan untuk mengetahui hasil belajar mahasiswa calon guru biologi prodi pendidikan biologi FKIP Universitas di Surakarta selama masa PTM terbatas T.A 2021/2022. Jenis penelitian ini adalah penelitian ex post facto. Subjek penelitian ini adalah 145 mahasiswa yang menempuh mata kuliah praktikum Sistematika Invertebrata. Data penelitian ini diperoleh dari dokumentasi hasil belajar mahasiswa kemudian dianalisis dengan analisis deskriptif. Hasil Penelitian menunjukkan bahwa hasil belajar mahasiswa praktikum Sistematika Invertebrata pada masa PTM terbatas T.A 2021/2022 dari ketiga komponen secara umum masuk dalam kategori sedang. Hasil postest memperoleh rata – rata 69.6, ujian responsi dengan rata – rata 63.2 dan rata – rata nilai akhir praktikum adalah 75.6. Hal ini menunjukkan bahwa hasil belajar mahasiswa selama masa PTM terbatas yang dihasilkan cukup baik.